11q deletions identify a new subset of B-cell chronic lymphocytic leukemia characterized by extensive nodal involvement and inferior prognosis - Döhner, Hartmut; Stilgenbauer, Stephan; James, Michael R.; Benner, Axel; Weilguni, Traudel; Bentz, Martin; Döhner, Konstanze; Hunstein, Werner; Lichter, Peter (Blood, 1997)
Deletions of the long arm of chromosome 11 (11q) are one of the most frequent structural chromosome aberrations in various types of lymphoproliferative disorders. However, in most conventional chromosome banding studies of B-cell chronic lymphocytic leukemia (B-CLL), 11q deletions were not identified as a frequent aberration. The objective of this study was to analyze the frequency and clinical impact of 11q deletions in B-CLL by interphase cytogenetics using fluorescence in situ hybridization (FISH). Mononuclear cells from 214 patients with B-CLL were studied by FISH using the yeast artificial chromosome (YAC) clone 755b11 from chromosome region 11q22.3-q23.1; we previously showed that this clone was contained within a 2- to 3-Mb sized segment of 11q commonly deleted in lymphoproliferative disorders. Forty-three of the 214 (20%) tumors exhibited 11q deletions; 11q deletions were the second most frequent chromosome aberration following 13q14 (RB1 and/or D13S25) deletions (45%); they were more frequent than trisomy 12 (15%) or deletion of 17p (TP53 gene) (10%). Patients with 11q deletions were younger (P = .01) and had more advanced clinical stages (P = .01). 11q deletions were associated with extensive peripheral, abdominal, and mediastinal lymphadenopathy (P < .001). Patients with 11q deletions had a more rapid disease progression as shown by a shorter treatment-free interval (9 months v 43 months; P < .001). The prognostic effect of 11q deletion on survival strongly depended on the age: in patients less than 55 years old, the median survival time was significantly shorter in the deletion group (64 months v 209 months; P < .001), whereas in patients ≥ 55 years old there was no significant difference (94 months v 111 months; P = .82). 11q deletions identify a new clinical subset of B-CLL characterized by extensive lymph node involvement. In younger B-CLL patients, this aberration is an important predictor of survival.